EKSTRA KURIKULER AUGMENTED REALITY UNTUK SMA SINAR DHARMA HIGH SCHOOL - Haris, Darius Andana; Wirawan, Jason; Sanjaya, Steven (Jurnal Serina Abdimas, 2023)
ABSTRACT The advancement of information and communication technology has become an important factor that is useful in various aspects. Everything that is done online also encourages progress in the field of information and communication technology. One form of product from information and communication technology is games. With the rapid development and popularity of games, it supports many game majors in college. At the high school level, especially upper secondary, game learning can be carried out through extracurricular activities. With extracurricular activities, high school students can develop their potential earlier and make the learning they get as a provision for entering the world of college later. This extracurricular activity also becomes one of the ways for students to support the improvement of non-academic achievements. Similar community service programs have been carried out previously for extracurricular teaching and have received a positive response. Sinar Dharma High School, which previously won a competition held through community service programs, now opens an extracurricular for game programming with Unity. The community service program is divided into several stages, namely needs research, material creation, teaching implementation, and final assessment.